(untitled) (TAMADDUN NURI JURNALI, 2024)
The article is devoted to the development of critical thinking skills in students during Russian language lessons. It examines the concept of critical thinking from philosophical, psychological, and pedagogical perspectives, analyzing its characteristics as a controlled, reasoned, and goal-oriented process. The significance of discussions and working with texts is highlighted as essential for building analysis, argumentation, and reflection skills. The article also explores specific techniques, such as the cluster method and the “INSERT” method, used to cultivate critical thinking through meaningful reading and writing.